Twin studies : research in genes, teeth and faces - Townsend, Grant; Pinkerton, Sandra K.; Rogers, James R. (James Robert), 1941-; Bockmann, Michelle R.; Hughes, Toby E. (University of Adelaide Press, 2015)
This volume is about an ongoing long-term research initiative led by researchers from the School of Dentistry at the University of Adelaide. The aim of this book is to provide an overview of the studies of the teeth and faces of Australian twins and their families that have extended over more than thirty years.